The Biophysical Modeling of Psychological Aspects - Vincze, Janos; Vincze-Tiszay, Gabriella (Advances in Social Sciences Research Journal, 2022)
The notion of stress has became as the same time very popular but is sometimes used improperly or with many exaggerations especially concerning the recommendations of practical solutions suggested for stress management. The stress producing stimuli, many physiological processes go into action, probably through different paths in close connection; the response is, therefore, an interaction between the organism and his environment. The emotional component takes part in the response reactions through the somatic effect of which it influences the behaviour. The man having lost his last connection with the world grieves duple and his environment must pay great attention not to lose also him. Every medico-surgical intervention belongs to the stress factors. Both contain psychopathological elements and a long psychotherapy accomplished by a specialist is needed, considerate-protective environment for the accommodation in the normal life, for the resocialization. The biological stress is a long succession of active, interactive mutual effect. This relation which always consists of the difference of value-power-intensity is, like an example of today, a chain of action of two fighter during which they get the offensive and defensive conduct in exchanged role. From the point of view of the human individual life the psyche (psychism) is a subsystem. If still we take it out of this relationship with investigational aim then we have to consider it a system.